Histochemical Studies on the Kidney of Emu (Dromaius novaehollandiae) - Archana, K.; Kumar, D. Pramod; Nagamalleswari, Y.; Raghavendar, K. B. P. (Indian Journal of Veterinary Anatomy, 2016)
Renal parenchyma exhibited positive PAS reaction in glomerular endothelium, basement membrane of visceral layer and mesangial cells. Similarly luminal border of PT, collecting tubules and basement membrane of PT were also positive to PAS. Moderate reaction for PAS-AB was noticed in the glomerulus followed by intense PAS-AB reaction in luminal borders of PCT and collecting tubules, whereas it showed a mild reaction in basement membrane of Bowman’s capsule. Kidney tubules displayed a moderate lipid activity. A mild to moderate acid phosphatase activity was seen in the glomerulus and kidney tubules, however the reaction was strong in renal capsule. Alkaline phosphatases activity was not appreciable.